Dolichoectasia of Basilar Artery in Hypertensive Putaminal Bleed - Yadav, Sugam; Chandra Sah, Ram; Tamrakar Karki, Karuna (Eastern Green Neurosurgery, 2024)
Dolichoectasia is a fusiform dilation of vascular structure that can occur anywhere in circulatory system. It is mostly detected and confirmed in the intracranial circulation in angiography. The vertebrobasilar system is the most common location. Putamen bleed has not been reported in association with vertebrobasilar dolichoectasia so far. Here, we report a rare case of detecting dolichoectasia of basilar artery in digital subtraction angiography with left putamen bleed in a middle-age hypertensive gentleman on irregular antihypertensive medication.